Vitamin D Status among Bangladeshi Adult Muslim Females Having Diabetes and Using Hijab - Shefin, Sultana Marufa; Qureshi, Nazmul Kabir; Nessa, Azimun; Latif, Zafar Ahmed (BIRDEM Medical Journal, 2018)
Background: This study was done to evaluate vitamin D level and status among Bangladeshi muslim women and to see association between vitamin D level and residence status, sunlight exposure, glycemic status, using hijab with exposed face and hands. Methods: This cross-section observational study was conducted during January 2015 to July 2017 among 353 Bangladeshi non-pregnant muslim female subjects aged e” 18 years who attended an urban endocrine clinic with complaints of myalgia, fatigability, muscle cramp etc. Subjects who were on vitamin D supplement/ treatment, suffering from mal-absorption syndrome, hepatic impairment, renal impairments, severe co-morbid conditions were excluded. Diabetic subjects were selected as per clinical history, HbA1c%, OGTT (oral glucose tolerance test) criteria or who already were receiving treatment for diabetes. Data were collected by face-toface interview and medical documents review and vitamin D level was tested with standard laboratory procedure. Subjects were enquired about using hijab with exposed face and hands with duration of years. Vitamin D status was defined as “deficient” with level of serum 25 (OH) vit D d”20 ng/ml, “insufficient” with level from 20.01 to 29.9 ng/ml and “sufficient” with level from 30 to 100 ng/ml. Data were analyzed with IBM SPSS for Windows version 20. The significance was tested by using un-paired T test and Chi-square test. Results: A total of 353 Bangladeshi muslim female were studied. Among them 332 (94.1%) were urban dwellers. Mean age was 40.66 ±13.80 years, mean vitamin D level was 17.27±7.47 ng/ml, while 71.67% subjects were vitamin D deficient and 22.66% subjects were insufficient. Residence status (urban and rural) showed no significant association with vitamin D level and status [p 0.074 and p 0.28 respectively]. Vitamin D insufficient subjects were more aged than deficient subjects [p 0.01]. Vitamin D level was not significantly different in regard to difference in sunlight exposure [p 0.70]. Diabetic (46.2%) and non-diabetic (53.8%) subjects had similar residence status [p 0.824]. Diabetic subjects were more aged than non-diabetic subjects [p 0.001] and vitamin D level was not significantly different among them [p 0.126 and p 0.28 respectively]. Among studied subjects 32.9% (n=116), mostly urban dwellers, never used hijab and they had mean vitamin D level as 17.04±7.77 ng/ml, while 30.3% (n=107) subjects used hijab more than 15 years with exposed face and hands and they had mean vitamin D level as 18.52±8.07 ng/ml. Difference of vitamin D levels and vitamin D were not significant among hijab users and non-users [p 0.16 and p 0.13 respectively]. Conclusion: The study revealed that most of the studied Bangladeshi muslim female urban dwellers had vitamin D deficiency and insufficiency which was not significantly influenced by glycemic status, residence status, level of sunlight exposure and using hijab. Large scale population based study is needed to elucidate findings of the current study. Birdem Med J 2018; 8(3): 203-209